KAJIAN NILAI PENDIDIKAN AGAMA HINDU DALAM UPACARA MENDEM ARI-ARI DI DESA TRUNYAN - Ida Bagus Gede Bawa Adnyana (Guna Widya: Jurnal Pendidikan Hindu, 2023)
The research entitled Study of the Value of Hindu Religious Education in the Mendem Ari-Ari Ceremony in Trunyan Village is a qualitative descriptive study. The purpose of this research is to find out; Facilities for Mendem Ari-ari Ceremony in Trunyan Village, Procedures for Mendem Ari-ari Ceremony in Trunyan Village, and Hindu Educational Values ​​in Mendem Ari Ari Ceremony in Trunyan Village. As a type of qualitative descriptive research, this research promises an in-depth analysis of the research subject in the form of qualitative data analysis with the stages of data collection, data reduction, and data analysis. The results of this study are various means, the stages of the Mendem Ari Ari ceremony in Trunyan Village contain Hindu educational values ​​which include four things namely; Value of Philosophy Education (Tatwa), Value of Ethics Education (Susila), Value of Ritual Education (Ceremony) and Value of Aesthetic Education (Beauty).